Semi fowler Position for Asthma Patient: Case Study - Antika, Ai Rindi; Ratnasari, Devi (Nursing Case Insight Journal, 2023)
Asthma is a chronic inflammatory disease of the respiratory tract reversible characterized by increased response of the trachea and bronchi to various stimulation. Signs and symptoms of bronchial asthma can vary from one individual to other individual based on severity and frequency of recurrence. Typical symptoms in sufferers include repeated shortness of breath, coughing, and wheezing. This case study aims to analyze care nursing for asthma patients. The author uses the analytical descriptive method in the form of a case study approach to nursing care for a patient which includes assessment, nursing diagnosis, nursing planning, nursing implementation, nursing evaluation, and the use of Evidence-Based Practice (EBP) interventions. Evaluation results can be resolved, this was indicated by a decreased complaint of shortness of breath in patients, improved respiration, increased saturation, no use of accessory muscles for breathing, and no nostril breathing. This showed that the semi-fowler position is a non-pharmacological therapy effective and proven to reduce shortness of breath in patients who experience respiratory problems such as asthma.